Geology, petrography, geochemistry and magnetic susceptibility of the Paleoproterozoic Granite São João, southeastern Amazonian Craton, Carajás Province - Lima, Paulo Henrique Araújo (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2013)
Teses